Ethnoscientific Study of Making Tuak (Massari) in Labissa Bone as a Biological Material Supplement - Putri, Nur Fisabilianti; Aminah, Sitti; Rijal, Syamsu; Yani, Ahmad; Arafah, Muhammad (BIOEDUSCIENCE, 2025)
Background: Tuak is a traditional drink found in Labissa Village, Ajangale District, Bone Regency. The process of taking tuak is called massari, the local wisdom of Labissa Village. The current independent Curriculum has the main characteristics of project-based learning: developing soft skills and student character, including integrating local wisdom in learning. This shows the need to explore local wisdom to be integrated into learning resources. Methods: This research aims to examine and analyze the process of making tuak, which will be incorporated as a biological supplement and is a type of ethnoscience research. The data source for this research used a purposive sampling technique. The data collection techniques used were observation, interviews, and literature study. Using two types of data: primary data and secondary data. Miles and Huberman's analysis techniques include data reduction, presentation, and conclusion drawing. The data validity test used is triangulation. Results: The research shows that making tuak (massari) can be integrated into biological materials. Conclusions: Making tuak (massari) in Labissa Village can supplement biological material, biodiversity, and biotechnology.